2012
DOI: 10.3109/00365599.2012.678382
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with an improved cancer-specific survival, but an increased rate of postoperative complications after surgery for renal cell carcinoma

Abstract: In this material, increasing BMI was associated with improved CSS for presumed radically treated patients. However, obese patients had a higher total rate of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…For patients with organ-confined but not advanced RCC, being overweight improved their cancer specific survival [24]. Another study also reported that cancer-specific survival time, but not overall survival time, was notably prolonged for patients with increasing BMI (>30 kg/m 2 ) who had received radical nephrectomy [25]. …”
Section: Reviewmentioning
confidence: 99%
“…For patients with organ-confined but not advanced RCC, being overweight improved their cancer specific survival [24]. Another study also reported that cancer-specific survival time, but not overall survival time, was notably prolonged for patients with increasing BMI (>30 kg/m 2 ) who had received radical nephrectomy [25]. …”
Section: Reviewmentioning
confidence: 99%
“…However, the influence of these risk factors on prognosis and survival in patients with RCC has not been well studied, especially before the early 2000s. Recently, a number of studies have provided evidence that being overweight or obese, as measured by the body mass index, is a favorable prognostic factor in patients with RCC (4-11). A few studies have shown that smoking may increase the risk of mortality in patients with RCC (12-14), but there have been very few studies and inconsistent conclusions concerning blood pressure (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Currently over one-third of the United States'population is obese [24]. There is a growing body of literature that supports the notion that there is a higher risk for preoperative complications including greater risk for wound infections, airway-related complications, deep vein thrombosis, and pulmonary embolus [6,[25][26][27][28][29][30][31]. Foley et al [32] was the first to describe the MI-TLIF using tubular retractors via a muscle splitting approach to decrease the amount of soft tissue injury.…”
Section: Discussionmentioning
confidence: 99%